Pengaruh Pemberian Rebusan Daun Katuk terhadap Produksi Asi Pada Ibu Nifas - Mariene Wiwin Dolang; Frisca P.A Wattimena; Erlin Kiriwenno; Sunik Cahyawati; Sahrir Sillehu (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Breastfeeding is the process of giving milk to babies with breast milk from the mother's breast since the baby is born and at least 6 months to 2 years or more. According to WHO, pregnant women and postpartum mothers should be informed about the benefits and advantages of breast milk, especially because breast milk provides the best nutrition for babies and protects against disease. According to the 2016 strategic plan, the national target of providing 80% exclusive breastfeeding has not yet reached the target. This study aims to determine the effect of giving decoction of katuk leaves on breast milk production in postpartum mothers in the working area of Suli Health Center. The research method in this research is pre-experimental design with one group pretest - posttest. The results showed that there was an effect of giving decoction of katuk leaves on breast milk production in postpartum mothers in the working area of the Suli Health Center with a value of p = 0.000 (p <0.05). The conclusion is that there is an effect of giving boiled water from katuk leaves on breast milk production in postpartum mothers in the working area of the Suli Health Center Keywords: Breastfeeding, Breast Milk Production, Decoction of Katuk Leaves, Postpartum Mothers